PENGARUH TONTONAN TELEVISI PADA ANAK DI DESA DALAM KAUM SAMBAS - Agustia Agustia (CV. ADIBA AISHA AMIRA, 2023)
This research uses quantitative. This type of research is associative. The population in this study amounted to 72. With a sample of 30 children. for the validity test, 10 children were taken. Data collection tools using indirect communication techniques, observation and validity and reliability tests. The results were tested by testing the validity and reliability as a prerequisite test. The data analysis technique was calculated using IBM SPSS Statistics Ver.24. The 1st and 2nd sub-problems were answered using a simple regression test while the 3rd sub-problem was answered using the one-sample Kolmogorov-Smirnov Test. Based on the results of the SPSS analysis, the sig value in the Annova table is 0.900 70.05 meaning that Ho is accepted and Ha is rejected. It means that there is no significant influence between television shows on children's morals. The relationship between variable television shows (X) on variable children's morals (Y). shown by the model summary table with an R of: 0.24 or 2.4% are in the